Bezafibrate for X-linked adrenoleukodystrophy. - Marc Engelen; Luc Tran; Rob Ofman; Josephine Brennecke; Ann B Moser; Inge M E Dijkstra; Ronald J A Wanders; Bwee Tien Poll-The; Stephan Kemp (PLoS ONE, 2012)
X-linked adrenoleukodystrophy (X-ALD) is caused by mutations in the ABCD1 gene and is characterized by impaired beta-oxidation of very-long-chain fatty acids (VLCFA) and subsequent VLCFA accumulation in tissues. In adulthood X-ALD most commonly manifests as a gradually progressive myelopathy, (adrenomyeloneuropathy; AMN) without any curative or disease modifying treatments. We recently showed that bezafibrate (BF), a drug used for the treatment of hyperlipidaemia, reduces VLCFA accumulation in X-ALD fibroblasts by inhibiting ELOVL1, an enzyme involved in the VLCFA synthesis. We therefore designed a proof-of-principal clinical trial to determine whether BF reduces VLCFA levels in plasma and lymphocytes of X-ALD patients. Ten males with AMN were treated with BF for 12 weeks at a dose of 400 mg daily, followed by 12 weeks of 800 mg daily. Every 4 weeks patients were evaluated for side effects and blood samples were taken for analysis. Adherence was good as indicated by a clear reduction in triglycerides. There was no reduction in VLCFA in either plasma or lymphocytes. Plasma levels of BF did not exceed 25 µmol/L. We concluded that BF, at least in the dose given, is unable to lower VLCFA levels in plasma or lymphocytes in X-ALD patients. It is unclear whether this is due to the low levels of BF reached in plasma. Our future work is aimed at the identification of highly-specific inhibitors of ELOVL1 that act at much lower concentrations than BF and are well tolerated. BF appears to have no therapeutic utility in X-ALD.ClinicalTrials.gov NCT01165060.